Electromagnetic navigation transthoracic needle aspiration for the diagnosis of pulmonary nodules: a safety and feasibility pilot study - Yarmus, Lonny B; Arias, Sixto; Feller-Kopman, David; Semaan, Roy; Wang, Ko Pen; Frimpong, Bernice; Oakjones Burgess, Karen; Thompson, Richard; Chen, Alex; Ortiz, Ricardo; Lee, Hans J (Journal of thoracic disease, 2016)
Pulmonary nodules remain a diagnostic challenge for physicians. Minimally invasive biopsy methods include bronchoscopy and CT guided transthoracic needle aspiration (TTNA). A novel electromagnetic guidance transthoracic needle aspiration (ETTNA) procedure which can be combined with navigational bronchoscopy (NB) and endobronchial ultrasound (EBUS) in a single setting has become available. A prospective pilot study examining the safety, feasibility and diagnostic yield of ETTNA in a single procedural setting. All patients enrolled underwent EBUS for lung cancer staging followed by NB and ETTNA. Feasibility of performing ETTNA and a safety assessment by recording procedural related complications including pneumothorax or bleeding was performed. Diagnostic yield of ETTNA defined by a definitive pathologic tissue diagnosis was recorded. An additional diagnostic yield analysis was performed using a cohort analysis of combined interventions (EBUS + NB + ETTNA). All non-diagnostic biopsies were either followed with radiographic imaging or a surgical biopsy was performed. Twenty-four subjects were enrolled. ETTNA was feasible in 96% of cases. No bleeding events occurred. There were five pneumothoraces (21%) of which only two (8%) subjects required drainage. The diagnostic yield for ETTNA alone was 83% and increased to 87% (P=0.0016) when ETTNA was combined with NB. When ETTNA and NB were performed with EBUS for complete staging, the diagnostic yield increased further to 92% (P=0.0001). This is the first human pilot study demonstrating an acceptable safety and feasibility profile with a novel ETTNA system. Further studies are needed to investigate the increased diagnostic yield from this pilot study.